Peripheral Blood Biomarkers Associated With Outcome in Non-small Cell Lung Cancer Patients Treated With Nivolumab and Durvalumab Monotherapy - Jiang, Meilin; Peng, Wenying; Pu, Xingxiang; Chen, Bolin; Li, Jia; Xu, Fang; Liu, Liyu; Xu, Li; Xu, Yan; Cao, Jun; Wang, Qianzhi; Li, Kang; et al. (Frontiers in Oncology, 2020)
Background: Selecting patients who potentially benefit from immune checkpoint inhibitors (ICIs) is critical. Programmed death ligand-1 (PD-L1) protein immunohistochemical expression on cancer cells or immune cells and next-generation sequencing-based tumor mutational burden (TMB) are hot spots in studies on ICIs, but there is still confusion in the testing methods. Because blood samples are much easier for clinical application, many potential peripheral biomarkers have been proposed. This study identified blood parameters associated with the outcome of non-small cell lung cancer (NSCLC) patients with ICI monotherapy. Materials and Methods: Data from 76 NSCLC patients were analyzed retrospectively. To assess the connection between survival and peripheral blood markers measured before the first and fifth doses of ICI treatment, we utilized Cox regression model survival analysis and receiver operating characteristic (ROC) curve analysis to assess the markers. Results: In the nivolumab cohort, the optimal cutoffs for predicting 11-month overall survival (OS) were 168.13 and 43 g/L for platelet-to-lymphocyte ratio (PLR) and albumin, respectively. When patients were grouped with PLR and albumin, a significant difference in SD-PR vs. PD rate was found between the high and low groups, which was not found when the patients were grouped by PD-L1 expression. Patients with high PLR (>168.13) or low albumin ( ≤ 43 g/L) before ICI had a significantly increased hazard of progression, separately (for PLR, P = 0.006; for albumin, P = 0.033), and of death (for PLR, P = 0.014; for albumin, P = 0.009) compared with those patients who had low PLR or albumin levels. More importantly, we found that a higher PLR (>168.13) before the fifth dose of ICIs was also a prognostic biomarker, which significantly correlated with shorter OS in both the nivolumab (P = 0.046) and durvalumab cohorts (P = 0.028). Conclusions: PLR and albumin may help in the stratification of high progression and death risk groups in advanced NSCLC patients treated with nivolumab and durvalumab monotherapy.